Conserving agricultural biodiversity in situ : a scientific basis for sustainable agriculture - Jarvis, D.; Sthapit, B.; Sears, L.; International Cocoa Organization; Common Fund for Commodities; International Plant Genetic Resources Institute (2000)
The purpose of the third annual planning meeting was for the national project partners of the project ”Strengthening the Scientific Basis of in situ Conservation of Agricultural Biodiversity” who have started data collection, together with technical advisers, IPGRI staff and relevant donors to: · compare and critique data collected by participating countries; · discuss methodologies for data integration within and among thematic areas; · synthesize methods used to enhance benefits from local crop diversity to all stakeholders;· discuss progress in increasing access, participation and decision-making for different gender, age and cultural groups; · discuss documentation options for in situ conservation on-farm; · share lessons learned to date from project implementation.